Biomass ash chemistry in chemical looping: Interaction between organic-K and Fe2O3/Al2O3 oxygen carrier using cellulose-CH3COOK as model compound. (August 2022) - Chen, Lu; Ge, Huijun; Li, Ping; Sheng, Changdong; Song, Tao
Abstract : Biomass fueled-Chemical Looping Combustion (CLC) provides a way for negative CO2 emission due to its property of carbon neutrality. Current knowledge is still lacking for organic K interaction behavior with oxygen carrier in CLC. Biomass ash chemistry mainly focusing on the interaction between organic-K and a Fe2 O3 /Al2 O3 oxygen carrier was investigated using cellulose-potassium acetate (CH3 COOK) as model compound. The decomposition characteristics of cellulose and CH3 COOK in the presence of oxygen carrier and interaction mechanism between K and Fe2 O3 /Al2 O3 were studied in a fixed bed at a reaction temperature of 900 °C. The influences of reducing atmosphere and addition of steam on the interaction behavior and mechanism were investigated. ICP-OES, XRD and cross section EDS/mapping analyses were employed to characterize the reacted oxygen carrier samples. Further, thermodynamic calculations were performed based on Gibbs energy minimization principle, to detect phase transition of biomass ash chemistry. The K accumulation in the oxygen carriers were 83.18% in dry condition, higher than that of 75.32% in wet condition when pure CH3 COOK was used. K2 CO3 formation may be directly derived from the decomposition of CH3 COOK or combination of K(g) with CO2 in the presence of lattice oxygen provided by oxygen carriers. Most of K turned into K2 CO3 and the melting of K2 CO3 caused the particles to stick together, creating agglomerations. Introduction of steam could suppress the agglomeration affinity. CH3 COOK was more converted into KOH in the case of water vapor. The steam atmosphere enhanced K penetration into the particles in comparison to dry atmosphere. Highlights: Interaction between organic-K and a Fe2 O3 /Al2 O3 oxygen carrier for Biomass-CLC. Cellulose-Potassium acetate (CH3 COOK) as model compound. Decomposition characteristics of cellulose and CH3 COOK with oxygen carrier. Influences of reducing atmosphere and addition of steam on interaction mechanism. Agglomeration mechanism was given based on experiments and analysis.